2003
DOI: 10.1046/j.1469-0691.2003.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of VITEK 2 for analysis of Enterobacteriaceae using the Advanced Expert System (AES) versus interpretive susceptibility guidelines used at Dynacare Kasper Medical Laboratories, Edmonton, Alberta

Abstract: This study demonstrated the benefits and limitations of the bioMérieux AES. Automated knowledge-based systems provide a useful laboratory tool for the interpretation of susceptibility results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Livermore et al (29) demonstrated the capacity of VITEK 2 to detect and interpret resistance mechanisms with a high level of accuracy and standardization. According to Blondel-Hill et al (30), the AES system is both adaptable and applicable in clinical microbiology laboratories to enhance the accuracy of susceptibility results and the clinical relevance of therapeutic recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Livermore et al (29) demonstrated the capacity of VITEK 2 to detect and interpret resistance mechanisms with a high level of accuracy and standardization. According to Blondel-Hill et al (30), the AES system is both adaptable and applicable in clinical microbiology laboratories to enhance the accuracy of susceptibility results and the clinical relevance of therapeutic recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The double-disc synergy test showed the highest specificity and positive predictive value among all test meth-VOL. 24,2011 EXPERT SYSTEMS IN CLINICAL MICROBIOLOGY 543 on May 9, 2018 by guest http://cmr.asm.org/ ods, i.e., 97% and 98%, respectively. Considering the rather low specificity observed by that study, those authors recommended the use of a manual test for confirmation once an organism is reported to be positive for ESBL production by any of the semiautomated systems.…”
Section: Detection Of Extended-spectrum ␤-Lactamases In Gramnegative mentioning
confidence: 99%
“…Recognition is there-VOL. 24,2011 EXPERT SYSTEMS IN CLINICAL MICROBIOLOGY 547 on May 9, 2018 by guest http://cmr.asm.org/ fore complicated by the highly efficient transmission of the MBL structural gene to strains in which the carbapenem-resistant phenotypes differ and in which a variety of other antibiotic resistance mechanisms may occur, including ESBLs. Espedido et al (78) showed that susceptibility profiles generated by diagnostic algorithms in commonly used automated bacterial identification systems such as the Phoenix NMIC/ID-101 panel and Vitek Legacy GNS-424, Vitek 2 AST-N044, and Vitek 2 AST-N019 Gram-negative cards failed to reliably identify a metallo-␤-lactamase in strains of the Enterobacteriaceae.…”
Section: Carbapenem Resistancementioning
confidence: 99%
“…Susceptibility/resistance is determined based on growth or inhibition of growth in the presence of antimicrobials at a limited range of concentrations straddling the breakpoint. Numerous evaluations of the Vitek system have been published (Blondel‐Hill et al, 2003; Bosman et al, 2014; Rennie et al, 2008). Fritsche et al (2011) reported on identification of bacterial pathogens from veterinary specimens.…”
Section: Introductionmentioning
confidence: 99%